MENELAAH FUNGSI SOLVABILITAS PADA LEMBAGA KEUANGAN DAN PERUSAHAAN SYARIAH - Tri Kusuma Alam, Cindy; Hasmawati, Hasmawati; B, Muchtar; Aria Mahbubi, Donny (At-Tawazun, Jurnal Ekonomi Syariah, 2024)
Solvency is the principal indicator in assessing the financial health of an entity, including financial institutions and companies based on sharia economics. This research aims to understand the meaning of solvency and its functions in maintaining financial stability and operations of financial institutions and Sharia companies. Using a qualitative approach with descriptive-analytical methods, this research analyzes data obtained through a study of related literature. The research results show that solvency plays an important role in managing risk, maintaining compliance with Sharia principles, and ensuring the sustainability of Sharia institutions and companies in facing financial challenges. Solvency also functions as an instrument to increase public trust and attract investors, especially because Sharia institutions must comply with principles such as the prohibition of usury, Gharar, and Maysir. However, there are several challenges in implementing solvency, especially in terms of limited Sharia financial instruments that can be used to manage risk effectively. This research concludes that solvency is a crucial element that has a direct impact on the performance and sustainability of financial institutions and Sharia companies, so innovation is needed in Sharia financial instruments and supporting regulations.